Meningkatkan Prestasi OSN Matematika Melalui Kolaborasi Guru dan Siswa di Kabupaten Malang - Solimun; Meilina Retno Hapsari; Mudjiono; Evellin Dewi Lusiana; Kamelia Hidayat; Celia Sianipar; Septi Nafisa Ulluya Zahra (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
This community service program aims to improve achievement in the National Science Olympiad (OSN) Mathematics through collaborative engagement between teachers and students in Malang Regency. The primary challenges identified include the lack of structured training programs, limited intensive mentoring by teachers, and insufficient competition simulations, which negatively affect students’ academic preparedness and psychological readiness. To address these issues, the program was implemented using integrated methods, including teacher workshops, intensive classes for students, collaborative discussion forums, competition simulations, and evaluation and monitoring based on statistical testing. The implementation emphasized strengthening teachers’ roles as active mentors while empowering students through targeted exercises aligned with authentic OSN competition contexts. Teachers were trained to design innovative mentoring strategies, develop problem-solving frameworks, and provide systematic feedback. Meanwhile, students participated in intensive training sessions and simulated competitions to enhance conceptual understanding and resilience under competitive pressure. The results demonstrate improved teacher competencies in developing effective coaching strategies, as well as increased readiness among junior and senior high school students in solving complex mathematical problems and managing competition-related stress. Beyond individual skill enhancement, the program fostered a collaborative, participatory, and sustainable learning ecosystem. Furthermore, this initiative contributes to improving mathematics education quality in Malang Regency by offering a structured coaching model that can be replicated in other schools and regions.